2015
DOI: 10.1007/s12020-015-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine effect of Zn2+ on the glucose-stimulated insulin secretion

Abstract: It is well known that zinc (Zn(2+)) is required for the process of insulin biosynthesis and the maturation of insulin secretory granules in pancreatic beta (β)-cells, and that changes in Zn(2+) levels in the pancreas have been found to be associated with diabetes. Glucose-stimulation causes a rapid co-secretion of Zn(2+) and insulin with similar kinetics. However, we do not know whether Zn(2+) regulates insulin availability and secretion. Here we investigated the effect of Zn(2+) on glucose-stimulated insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Enrichment analysis of the differential genes in NOD vs C57Bl/6 islets revealed dysregulation of genes related to metal ion transport, in line with recent studies showing that pancreatic changes in Zn 2+ levels influence the availability and action of insulin [30,31]. In addition, genes implicated in the regulation of protein kinase activity were affected in NOD islets, which could lead to disturbances in the regulation of several molecular processes.…”
Section: Discussionsupporting
confidence: 79%
“…Enrichment analysis of the differential genes in NOD vs C57Bl/6 islets revealed dysregulation of genes related to metal ion transport, in line with recent studies showing that pancreatic changes in Zn 2+ levels influence the availability and action of insulin [30,31]. In addition, genes implicated in the regulation of protein kinase activity were affected in NOD islets, which could lead to disturbances in the regulation of several molecular processes.…”
Section: Discussionsupporting
confidence: 79%
“…In-vitro environments increasing the extracellular Zinc concentration is known to increase the free insulin concentration in the immediate vicinity of β-cells, mediated by enhanced Zinc-insulin dissociation [ 63 ]. However, glucose stimulated insulin secretion in β-cells of the pancreas is inhibited by Zinc, suggesting that co-secreted Zinc acts in an autocrine inhibitory modulator [ 64 , 65 ]. In pancreatic β-cells of mice and clonal HIT-T15 β-cells, KCl and glucose induced an increase in free cytosolic Zinc levels, which facilitated the processing and/or storage of insulin [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six insulin monomers congregate in β-cells into a hexamer with two zinc ions in the center, and this form is stored and transported across the cell membrane as an insulin-zinc crystal in the normal functioning of β-cells. Slepchenko et al [ 120 ] have shown inhibition of the zinc feature upon further glucose-stimulated secretion of insulin. After the zinc–insulin complexes have been secreted, they start to dissociate; only the insulin monomer is an active form of the hormone.…”
Section: Introductionmentioning
confidence: 99%